2020
DOI: 10.1021/acs.est.9b06837
|View full text |Cite
|
Sign up to set email alerts
|

Effective Modeling Framework for Quantifying the Potential Impacts of Coexisting Anions on the Toxicity of Arsenate, Selenite, and Vanadate

Abstract: and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commercial gain • You may freely distribute the URL identifying the publication in the public portal ? Take down policyIf you believe that this document breaches c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Denitrification, which sequentially transforms nitrate to final nitrogen, is catalyzed by a series of specific enzymes, some of which (e.g., NarG and NirS) have also been reported to catalyze V­(V) reduction. , Therefore, denitrifying microbes widely distributed in the environment are expected to be able to reduce V­(V), which can be identified by genes encoding these enzymes. Combined pollution is common in V-polluted environments, and the efficacy of the screened species for coexisting pollutants should also be evaluated for successful remediation. Most V bioremediation attempts have been conducted in laboratories, and pilot-scale tests or practical applications that consider the site characteristics are essential.…”
Section: Implications and Future Perspectivesmentioning
confidence: 99%
“…Denitrification, which sequentially transforms nitrate to final nitrogen, is catalyzed by a series of specific enzymes, some of which (e.g., NarG and NirS) have also been reported to catalyze V­(V) reduction. , Therefore, denitrifying microbes widely distributed in the environment are expected to be able to reduce V­(V), which can be identified by genes encoding these enzymes. Combined pollution is common in V-polluted environments, and the efficacy of the screened species for coexisting pollutants should also be evaluated for successful remediation. Most V bioremediation attempts have been conducted in laboratories, and pilot-scale tests or practical applications that consider the site characteristics are essential.…”
Section: Implications and Future Perspectivesmentioning
confidence: 99%
“…From that point on, the BLM framework was extended to soils for quantifying metal mixture toxicity. Recently, a BLM-Toxic Unit model has been successfully developed to quantify the toxicity of As-Se mixtures under the influence of varying anion exposures, explaining more than 77% of the observed variation in toxicity (Ji et al, 2020). This is the first systematic study on the single and mixture toxicity of anionic metal(loid)s under the influences of varying anion concentrations.…”
Section: Application In Assessment Of Metal Toxicitymentioning
confidence: 99%
“…Substantial advances have been made in understanding and characterizing the role of TMFs using bioavailability models for metals (Adams et al, 2020 ; Di Toro et al, 2001 ; Van Genderen et al, 2020 ; Veltman et al, 2010 ) that are applicable to other analyte groups. Considering the multitude of studies that have assessed the impact of TMFs on inorganic anions (such as nitrate, sulfate, chloride, and fluoride [Baker et al, 2017 ; Ji et al, 2020 ; Mount et al, 2016 ; Soucek et al, 2011 ]), the application of similar frameworks may improve our understanding of inorganic anion toxicity to aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple linear regression approaches have been widely adopted to assess the bioavailability of metals (Brix et al, 2017 ; DeForest et al, 2018 , 2020 ; Gillio Meina et al, 2020 ; USEPA, 2018 ), and it is recognized that bioavailability models are potentially beneficial to other classes of toxicants as well (Brix et al, 2020 ). For example, recent research has demonstrated the applicability of bioavailability models for establishing protective values for anionic metalloids (Brix et al, 2001 ; Ji et al, 2020 ; Wang & Song, 2021 ). These studies demonstrate that the bioavailability of anions in freshwater can be mediated by the presence of other water quality parameters and that TMFs are critical to determining robust protective values for inorganic anions.…”
Section: Introductionmentioning
confidence: 99%